1978
DOI: 10.1016/0021-9614(78)90116-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity and thermodynamic properties of CrSb2 from 5 to 1050 K. Magnetic transition and enthalpy of decomposition

Abstract: The heat capacity of CrSbz has been measured by adiabatic calorimetry from 5 to 991.3 K. At the latter temperature the CrSb,-phase decomposes into the CrSb-phase and an antimonyrich melt. The heat capacity of the two-phase mixture was measured from 991.3 to 1050 K. The heat capacity of CrSb, shows a small sharp h-type transition with a maximum at 274.1 K where the change from the antiferromagnetic to the paramagnetic state occurs. Thelow entropy of the clearly cooperative part of the transition, A& = 0.12 calt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…3), which is well consistent with pervious result reported by other authors [21]. The observed anomaly was proved to originate from antiferromagnetic transition [22,24,28] and the plateau was related to an electronic change of the electron-spin system in the antiferromagnetic semiconductor [29]. In comparison, the resistivity for CrSb 2−x Sn x has a similar temperature dependence, that is, it shows semiconductor-like behavior, and the plateau (as shown in Fig.…”
Section: Phase Determination and Measurements Of Lattice Parameters Asupporting
confidence: 92%
See 1 more Smart Citation
“…3), which is well consistent with pervious result reported by other authors [21]. The observed anomaly was proved to originate from antiferromagnetic transition [22,24,28] and the plateau was related to an electronic change of the electron-spin system in the antiferromagnetic semiconductor [29]. In comparison, the resistivity for CrSb 2−x Sn x has a similar temperature dependence, that is, it shows semiconductor-like behavior, and the plateau (as shown in Fig.…”
Section: Phase Determination and Measurements Of Lattice Parameters Asupporting
confidence: 92%
“…Therefore, the left two unpaired electrons per Cr do not contribute to the bond, CrSb 2 has a d-state manifold per Cr atom 3d 2 in CrSb 6 -octahedra [19,[24][25][26], taking a localized high-spin configuration [20,22,27]. Moreover, CrSb 2 is an antiferromagnetic compound with the Neel temperature of T N = 273 ± 2K [21,22,24,28]. The magnetic properties of Cr 1−x Fe x Sb 2 (0 ≤ x ≤1) was reported by Kjekshus et al [24], which showed that the Neel temperature decreased with increasing Fe content and diminishes to zero at about x = 0.5.…”
Section: Introductionmentioning
confidence: 97%
“…The compounds FeSi, FeSb 2 and CrSb 2 are narrow gap semiconductors, Eg ≈ 0.1 eV, with dominant 3dcharacter of the electronic states near the conduction and valence band edges and interesting magnetic and transport properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Both CrSb 2 and FeSb 2 crystallize in the orthorhombic marcasite structure (P nnm space group), while FeSi crystallizes in the cubic B20 structure (P 2 1 3 space group).…”
Section: Introductionmentioning
confidence: 99%
“…4), which is well consistent with pervious result reported by other authors (the observed anomaly for CrSb 2 is around 273 K [18]). The observed anomaly was proved to originate from antiferromagnetic transition [19,21,22] and the plateau was related to an electronic change of the electron-spin system in the antiferromagnetic semiconductor [23]. By comparing curve (a) with curves (b)-(d) in Fig.…”
Section: Phase Determination and Measurements Of Lattice Parametersmentioning
confidence: 91%
“…CrSb 2 has the orthorhombic marcasite structure (crystal group Pnnm): each Cr atom has a distorted octahedral coordination of six nearest-neighbor Sb atoms; each Sb atom is tetrahedrally coordinated by three Cr atoms and one Sb atom [16][17][18][19][20]. CrSb 2 is an antiferromagnetic compound with the Neel temperature of T N = 273 ± 2 K [18,19,21,22]. The magnetic properties of Cr 1−x Fe x Sb 2 (0 ≤ x ≤ 1) was reported by Kjekshus et al [21], which showed that the Neel temperature decreased with increasing Fe content and diminished to zero at about x = 0.5.…”
Section: Introductionmentioning
confidence: 99%